Aku cinta pahlawan bangsa / Eviliana Elsiva, Tsabita El Khansa; editor, A. Saibani, Junbitung; ilustrasi, Zafran Aidil - EVILIANA ELSIVA; Tsabita El Khansa; Saibani, A; Junbitung; Zafran Aidil (Bee Media Pustaka, 2016)
24 hlm. : ilus. ; 20 cm.